(untitled) (Research, Society and Development, 2020)
This study aimed to identify the changes in flexibility levels in Jazz dancers submitted to the proprioceptive neuromuscular facilitation (PNF) method. It is a descriptive field research, with a quantitative approach, composed of 28 dancers, of both sexes, aged between 15 and 40 years, practicing jazz for a minimum of five years, divided randomly into three Groups: Control group (CG) practitioners without PNF method intervention; G2S group: dancers who performed two sets of PNF per session and G3S Group: dancers who performed three series per PNF sessions. To characterize the sample, the following parameters were used: age, height (in meters), body weight (in kg), and body mass index (BMI in kg/m2). The assessment of hip flexibility was performed by goniometry, assessed by session and by progression (after four weeks). It can be inferred that the PNF method promoted the improvement of the angular flexibility in the hip of all the dancers evaluated in this sample, both per session (acute) and after four weeks of (chronic) methodological application. It was evidenced that the number of PNF sessions was relevant in the amplification of the acute flexibility, however unimpressive when compared after four weeks of methodological application in this sample. Moreover, significant gains in angular flexibility occurred from the fourth session of PNF. It is worth mentioning that the jazz classes promoted significant gains in the flexibility of the dancers, although with inferior gains in relation to the groups of methodological application.